COMPARISON OF HYSTEROSALPINGOGRAPHY AND ULTRASOUND IN EVALUATION OF UTERINE ABNORMALITIES IN PRIMARY AND SECONDARY INFERTILE PATIENTS (The Research of Medical Science Review, 2025)
Background: The leading issue that every couple is experiencing in present era is infertility. Many factors contribute in infertility. It is important to diagnose the underlaying causes that lead to inability to conceive. The primary modes of diagnosis include Ultrasound and Hysterosalpingography. But which modality is better for ruling out the infertility is point of debate. Objective: To Compare diagnostic effectiveness of Ultrasound and Hysterosalpingography in detecting uterine abnormalities among Primary and Secondary Infertile women. Methodology: 73 patients were examined on Ultrasound in Dr. Essa Lab Lahore and then referred for Hysterosalpingography to Punjab Radiology and Lab Lahore. Patients with Primary and secondary infertility between the age of 18 to 45 were included whereas pregnant women and women with PID and GTI were excluded. The data were processed in SPSS version 25 by using descriptive and frequencies and Chi-Square test for comparison of USG and HSG. Results: In the total 73 patients, 36 patients were of the age between 26-35 years. Primary Infertility constituted 63% out of total patients. According to the history, 37% patients presented more than one symptom. On Ultrasound, 49 patients were shown normal. 8 patients diagnosed with ovarian cysts which were the highest percentage. While No Fallopian pathology was diagnosed. On HSG, 74% patient were normal. Tubal pathologies constituted 17.8% of patients, were the most common. While, ovarian pathology could not be seen on it. Conclusion: This study Concludes that Ultrasound has higher sensitivity in diagnosing uterine and cervical pathologies but not tubal pathologies. While, Hysterosalpingography helps in diagnosing Tubal pathologies and congenital Uterine anomalies more efficiently